Time-Management Skills and Lecturer Productivity in Federal Colleges of Education in South-Western Nigeria. (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Lecturer Productivity (LP), measured by Research Output (RO) and Teaching Effectiveness (TE), is crucial to the career progression of lecturers in tertiary institutions in Nigeria, including Colleges of Education (CoEs). However, literature indicate that LP is low across CoEs, particularly in Federal Colleges of Education (FCEs) in south-western Nigeria. Prior studies on LP have largely focused on demographic factors, self-esteem, psychological well-being, and hard skills among university and polytechnic lecturers, with little attention paid to the relationship between Time Management Skills (TMS) and LP in FCEs in south–western Nigeria. A descriptive survey design was employed in the study. The four first-generation FCEs (FCE (Special) Oyo, FCE Abeokuta, FCE Technical Akoka and Adeyemi College of Education (ACE) Ondo) were purposively selected. One hundred and nineteen Heads of Department (HoDs) were also enumerated. Proportionate-to-size sampling was used to select 10% of the lecturers and NCE III students, yielding sample sizes of 149 and 803, respectively. The instruments used were the TMSQ (0.78) and the LPQ (0.82) scales. The quantitative data were analysed using descriptive statistics and Pearson product-moment correlation. The findings of this study indicated that TMS (2.65) and LP (3.02) were high against the threshold of 2.50. Time management significantly correlated with LP in FCEs in south-western Nigeria. The study therefore recommended, among other things, that lecturer productivity could be increased by organising workshops and seminars for the lecturer on planning, organising, and time management.